ENKULTURASI: POLA PEWARISAN KESENIAN TARAWANGSA DI DESA WISATA RANCAKALONG - Desandra; Saryanto; Supriadi, Didin (Jurnal Penelitian Musik, 2020)
To maintain the Tarawangsa Art, real effort and appreciation must be made by the community, especially the younger generation, the government and also schools to inherit and preserve Tarawangsa Art so that this art will not become extinct and remain a cultural identity of Indonesia. One effort that can be done is through the regeneration of Tarawangsa Artists towards the young generation. The younger generation has a very important role in the preservation of Tarawangsa Art. The type of research method used in this study is qualitative ethnographic approach. Data collection was carried out using observations, in-depth interviews, literature studies and documentation. In the process of analyzing the data obtained there are several stages including data reduction, data presentation, and inference (verification). The results of research and data analysis in this study concluded that the process of inheritance of tarawangsa artistry carried out by Mr. Pupung applied a learning by doing approach, meaning that they learned the material provided through direct practical activities. In addition, there are 6 stages of learning in the process of inheritance carried out by Mr. Pupung, namely juntrung, ngararaba, nyoba-nyoba, mitemeyan, ngaderes, and hatam. The process of inheritance carried out by Mr. Pupung is by seeing and hearing, not using number notation.